Konstruksi Realitas Budaya Film Jumbo dalam Pemberitaan Media Online detik.com - Sinta Dwi Utami (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study aims to analyse how detik.com constructs cultural reality in its coverage of the film Jumbo. The study was conducted because mass media plays a significant role in shaping public understanding of the film. The  media not only conveys factual information but also constructs cultural reality. Using the Reality Construction Theory of Peter L. Berger and Thomas Luckmann, this study maps three main phases of news coverage: pre-screening, screening, and post-screening. With 34 articles as research objects, data were collected through articles published between February 13 and April 30, 2025. With a qualitative approach, content analysis was used to identify news units, dominant narratives, themes, and interpretations of meaning and symbols. The results showed that the externalization process occurs through the promotional narrative and representation of Jumbo as a national film. Objectivation is realized through the strengthening of success symbols, such as viewers, symbolic awards, and comparisons with other popular films. The internalization process is formed through the collective image of Jumbo as a representation of the successful national animation industry. Explicitly, the media framed the film Jumbo as an achievement of the national film industry, and implicitly, the narrative strengthened the construction of Indonesia’s popular culture.